(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: Communication among healthcare team members is crucial for effective patient care. It helps ensure that everyone involved in the healthcare process is aware of the patient’s needs and treatment plan, which increases the likelihood of positive outcomes and reduces the risk of medical errors. Strong communication can help build trust and collaboration among healthcare team members, which can improve job satisfaction and lead to better patient outcomes. Aim: To study and explore the effect of an educational campaign on interpersonal communication skills among healthcare professionals in Jeddah, KSA. Methods: A quasi-experimental pre- and post- study was carried out on a convenient sample of 150 healthcare professionals. A specially prepared self-administered, pre-coded, closed-ended, pilot-tested, reliable questionnaire format was used. Self- assessment communication skills inventory questionnaires were completed initially in the pre-study phase and at the end of a specifically arranged educational campaign as the post-study phase. To control for potential confounding factors, multivariate analyses using a forward stepwise (Wald) method were carried out to determine independent predictors of interpersonal communication skills among the healthcare professionals. Results: There was a significant improvement of the measured responses to the interpersonal communication skill inventory in all its domains, namely: sending a clear message (p=0.000), listening (p=0.000), giving and receiving feedback (p=0.000) and handling emotional reactions (p=0.000). Significant independent predictors of interpersonal communication skills were nationality, mother language, specialty, qualification, daily working hours, number of monthly shifts and perceived satisfaction with the work environment. The mean evaluation of the whole campaign out of 10 was 9.6 (4.85), with a mean percent score for evaluation of 77.6 (22.15). Conclusion: these educational campaigns for the development of interpersonal communication skills have desirable effects on healthcare professionals’ communication abilities and capabilities. Healthcare organizations should invest in training programs that develop healthcare professionals’ communication skills to improve healthcare quality and patient safety.